2011
DOI: 10.33899/magrj.2011.30168
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Magnesium in Increasing of Phosphorus Fertilizer Efficiency and Wheat Yield

Abstract: The study was conducted during the growing season 2003 to study the influence of four levels of P (0, 60, 100 and 140 kg ha -1 ) and four levels of Mg (0, 40, 80 and 120 kg ha -1 ) at two locations (Bakrajow and Kalar) on growth and yield of wheat and phosphorus fertilizer efficiency. The results indicated to the response of wheat to phosphorous fertilizer at Bakrajow location only. While the application of 40 kg Mg ha -1 caused significant increase in wheat yield at Bakrajow location only. The highest phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…In addition, the Mg present in struvite may be another contributor of the higher P uptake due to the synergistic effect of Mg on P absorption [13]. This is verified by Rasul et al (2011) [23], who observed Mg application could improve the PUE of wheat by over 55%. So, struvite application is advantageous in soils and crops with high Mg and P demand, and under acid and neutral soil conditions.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, the Mg present in struvite may be another contributor of the higher P uptake due to the synergistic effect of Mg on P absorption [13]. This is verified by Rasul et al (2011) [23], who observed Mg application could improve the PUE of wheat by over 55%. So, struvite application is advantageous in soils and crops with high Mg and P demand, and under acid and neutral soil conditions.…”
Section: Discussionmentioning
confidence: 70%